Everybody hurts sometimes: perceptions of benefits and barriers in telemedical consultations - Rohowsky, Anna; Offermann, Julia; Ziefle, Martina (Frontiers in Public Health, 2023)
Introduction: Shifts in the age structure, rising needs of care and support, and a lack of (in)formal caregivers require innovative solutions to relieve the whole healthcare system. Applying digital approaches, such as telemedicine, has the potential to support people in need of care, to relieve caregivers in families and professional environments, and to assist medical professionals in their working everyday life: e.g., using telemedicine for acute consultations could contribute to avoid hospitalizations of older people, whereas consultations with the general practitioner could reduce efforts and relive medical personnel. Beyond technical opportunities and potential, the acceptance of future users represents a prerequisite for a sustainable adoption of such innovative approaches, especially in sensitive contexts such as life in older age in nursing homes.Methods: This study aimed at collecting users' perceptions and evaluations of telemedicine in nursing homes. Two scenarios of telemedical consultations were applied which were either carried out by an emergency physician in acute situations or by the attending general practitioner.In a first approach, advantages and disadvantages of telemedicine were collected with the help of a qualitative interview study (N=12) with laypersons and medical staff. The identified acceptance-relevant factors were then quantified in a second study using an online questionnaire (N=204). Results: Outcomes revealed that both types of telemedicial consultations would be gladly used. However, for telemedical consultations in acute situations, the perceived disadvantages outweighed the advantages; for telemedical consultations with the general practitioner, the advantages outweighed the disadvantages. A prominent barrier in both scenarios was perceived impersonality, which limited the willingness to use. Nevertheless, participants indicated that telemedical consultations can be a support for nursing staff. Discussion: Outcomes may help to derive specific implications and recommendations to develop and realize digital technologies tailored to the requirements, needs, and wishes of diverse stakeholders (i.e., patients, medical professionals) as potential future users.